A common European Curriculum for Dental Hygiene ‐ Domain I: Professionalism. (19th September 2020) - Öhrn, Kerstin; Danielsen, Bo; Field, James
Abstract: This position paper outlines the areas of competence and learning outcomes of the Common European Curriculum for Dental Hygiene (CECDH) that specifically relate to Professionalism. Professionalism is a commitment to a set of values, behaviours and relationships, which underpin the trust that the public hold in Dental Care Professionals. Shortcomings within this domain are often responsible for patient dissatisfaction, concern and complaint—and emphasis is placed on the importance of embedding these values from an early stage within the curriculum.